Activities of civic organizations in the field of protection of prisoners and rehabilitated persons in the soviet period legal assessment of russian crimes in Ukraine - Demyanchuk T. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the publication is to reveal the degree of involvement of public institutions in the protection of the rights of prisoners and rehabilitated persons in the Ukrainian SSR in the 1960s-1980s. Methods. The methodological basis of the research was a set of principles of historicism, objectivity, as well as general scientific, special scientific and philosophical methods. Results. It was established that in the conditions of the liberalization of social relations in the second half of the 1950s, the degree of involvement of public organizations in working with prisoners was fixed at the legislative level, but the norms of the criminal and correctional and labor codes contained significant contradictions, in particular, the Criminal Code of the Ukrainian SSR provided for the serving of a conditional sentence or early dismissal in the workforce of a separate enterprise, while the Correctional Labor Code only mentioned the possibility of involving labor unions in such work. Only after the creation of the Ukrainian Helsinki Group (later the Ukrainian Helsinki Union) and the "Memorial" society can we say that a real struggle for the rights of prisoners appeared. Legally, public organizations could not fundamentally influence the work of the criminal-executive system, but they showed its totalitarian and anti-human character, contributed to the collapse of this system and the USSR itself. Originality. Information is provided about the process of formation of public organizations in the Ukrainian SSR and the degree of their involvement in protecting the rights of persons who served sentences or were rehabilitated. Practical significance. The results of the research can be used for the preparation of lectures and special courses on the history of the state and law, popularization of the historical past, preservation of historical memory and condemnation of the actions of Soviet leaders.